Studi Penangkapan Ayam Hutan Merah di Kabupaten Kaur Bengkulu - Miki Suhadi (Wahana Peternakan, 2019)
The objective of this research was to gather information about capturing techniques used by the local communities in Kaur District. Respondents were chosen by using snowball sampling method. Variables observed were equipment used by respondents, the time and location of capturing red jungle fowl. The result showed that the equipment used by the respondents are food supplies (rice and water), weapons (machetes, knives, matches), and clothing (hats , jackets, trousers, raincoats) and red jungle fowl hooks, nets, racit, sangkek and bags. Most of respondents chose the location of luring jungle fowl in the plantation area. Keywords: catching, equipment, red jungle fowl